1997
DOI: 10.1002/j.1550-8528.1997.tb00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Concerns and Health‐Compromising Behaviors among Overweight and Nonoverweight Adolescents

Abstract: Objective: To compare weight-specific and global psychosocial concerns and health-compromising behaviors among overweight and nonoverweight youth across gender and ethnicity. Methods: A cross-sectional schoolbased survey of 31,122 adolescents in grades 7 to 12. Based on self-reported heights and weights, respondents were categorized as nonoverweight (body mass index (BMI) 4 5 t h percentile), moderately overweight (85th percentile 95th percentile). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 45 publications
7
80
1
1
Order By: Relevance
“…The findings are consistent with those who have failed to find increased distress in overweight adolescents 7 and contrary to findings in overweight children, 20 suggesting that eating disorder symptoms are not increased or elevated in this group. However, the current findings do indicate that some of the cognitions associated with eating disorders (and perhaps with other psychopathology) are present in the overweight group and not in the normal weight group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings are consistent with those who have failed to find increased distress in overweight adolescents 7 and contrary to findings in overweight children, 20 suggesting that eating disorder symptoms are not increased or elevated in this group. However, the current findings do indicate that some of the cognitions associated with eating disorders (and perhaps with other psychopathology) are present in the overweight group and not in the normal weight group.…”
Section: Discussionsupporting
confidence: 86%
“…To date the findings remain ambiguous. In their crosssectional school-based survey exploring psychosocial concerns and health-compromising behaviours, Neumark-Sztainer and colleagues 7 found that psychosocial concerns such as emotional well-being, suicidal ideation, peer concerns and future job concerns did not differ significantly between overweight and nonoverweight adolescents. However, their results did suggest that overweight adolescents were more likely than their normal weight counterparts to express weight-specific concerns and engage in behaviours such as chronic dieting and binge eating.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous cross-sectional studies have observed that binge eating is more common among overweight adolescents and adults than their leaner peers. 2,26,27 Because weight gain results from an imbalance between energy intake and energy output, it seems likely that binge eating should result in weight gain. Nevertheless, we are unaware of other prospective studies on binge eating and weight change.…”
Section: Discussionmentioning
confidence: 99%
“…14 This general rise in obesity is likely to have longlasting physical and mental health consequences for the population. Even during childhood, obesity is closely related to increased risk of CVD and noninsulin dependent diabetes mellitus (NIDDM), 15 ± 17 psycho-social concerns 18 and the increased risk of some forms of cancer. 19,20 There have been two recent studies which provide a clear indication of the epidemiological impact of childhood obesity on overall health risk.…”
Section: Epidemiology and Health Consequences Of Pediatric Obesitymentioning
confidence: 99%